Impact of tumor site on the prognosis of small bowel adenocarcinoma. Issue 6 (December 2019) - Falcone, Rosa; Romiti, Adriana; Filetti, Marco; Roberto, Michela; Righini, Riccardo; Botticelli, Andrea; Pilozzi, Emanuela; Ghidini, Michele; Pizzo, Claudio; Mazzuca, Federica; Marchetti, Paolo
Background: Because of a lack of large-scale prospective studies there is no clear indication about the management of patients with small bowel adenocarcinoma (SBA). This study evaluated clinical outcome of patients diagnosed with SBA at our institution. Methods: Clinicopathologic features, treatments, and clinical outcome of patients diagnosed with SBA between 2006 and 2017 were retrospectively analyzed. Median time of survival was calculated and compared using the log-rank test. Multivariate Cox regression was used to test independence of significant factors in univariate analysis. Results: Forty patients were included in the study; the majority (82.5%) had a tumor in the duodenum (including ampulla of Vater) and an early stage disease at the diagnosis. Median overall survival (OS) in the whole study population was 26.5 months. Patients with a tumor of the lower part of the small intestine (jejunum, ileum, and appendix) showed a better OS compared with that of patients with upper SBA (40 months vs 26 months, respectively; P =0.09). Primary tumor site and stage were independent predictors of OS. Conclusions: Our results suggest a prognostic role for the primary tumor site. This finding deserves to be further investigated to ensure better classification as well as more effective management strategies for SBA.